2020
DOI: 10.1148/radiol.2020191740
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Benign from Malignant Pulmonary Nodules by Using a Convolutional Neural Network to Determine Volume Change at Chest CT

Abstract: Background: Deep learning may help to improve computer-aided detection of volume (CADv) measurement of pulmonary nodules at chest CT.Purpose: To determine the efficacy of a deep learning method for improving CADv for measuring the solid and ground-glass opacity (GGO) volumes of a nodule, doubling time (DT), and the change in volume at chest CT. Materials and Methods:From January 2014 to December 2016, patients with pulmonary nodules at CT were retrospectively reviewed. CADv without and with a convolutional neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…When successfully applied, it is expected to improve diagnostic accuracy and reduce unnecessary invasive procedures and costs and anxiety of patients. Several studies have revealed the predictive value of CNNs and the promising prospects they afford for lung lesion differentiation (15)(16)(17)(18). However, (1) these models lack interpretability and are often referred to as "black boxes", which renders them difficult for the users to understand; (2) no specific emphasis has been given to distinguishing benign from malignant lesions manifesting as solid, indeterminate pulmonary lesions.…”
Section: Introductionmentioning
confidence: 99%
“…When successfully applied, it is expected to improve diagnostic accuracy and reduce unnecessary invasive procedures and costs and anxiety of patients. Several studies have revealed the predictive value of CNNs and the promising prospects they afford for lung lesion differentiation (15)(16)(17)(18). However, (1) these models lack interpretability and are often referred to as "black boxes", which renders them difficult for the users to understand; (2) no specific emphasis has been given to distinguishing benign from malignant lesions manifesting as solid, indeterminate pulmonary lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently,Most studies of pulmonary nodules focus on the discrimination of benign and malignant nodules, and pay insu cient attention to the classi cation and diagnosis of benign nodules [12,13] . In order to reduce medical waste under the requirements of precision medical model, it is necessary to further classify and diagnose benign nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Ohno et al approached this issue by calculating the volume change and volume doubling time of pulmonary nodules, assisted by the DL technique applied to computeraided detection of volume (CADv) measurements (67). They reported that the AUC and accuracy of total volume change per day calculated by the CADv with the DL method (AUC, 0.94; accuracy, 90%) were significantly higher than those of the volume doubling times with CADv using the DL method (AUC, 0.67; accuracy, 83%), and CADv not using the DL method (total volume change per day: AUC, 0.69 and accuracy, 67%; volume doubling time: AUC, 0.58, and accuracy, 65%) (67).…”
Section: Malignancy Prediction For Indeterminate Lung Nodulesmentioning
confidence: 99%